The study of prevalence of metabolic syndrome among nurses of Shahid Mohammadi Hospital of Bandar Abbas city, Iran - Amineh Amiri (Majallah-i Bālīnī-i Parastārī va Māmāyī, 2017)
Background and aims: The metabolic syndrome is a combination of factors such as abdominal obesity, hypertension, dyslipidemia and hyperglycemia which increase the risk of many diseases such as diabetes, heart disease and stroke.